Reducing Court Delays : Five Lessons from the United States - Messick, Richard (World Bank, Washington, DC, 2012)
For almost 50 years judges, lawyers, and policymakers in the United States have experimented with ways to speed up the processing of civil and criminal cases. Several lessons have emerged from this effort: a) Delays cannot be legislated away. b) Commitment is essential. c) Incentives must be addressed. d) Solid empirical analysis is crucial. e) Successful programs may not reduce delays. Perhaps the most surprising is that a well-conceived delay reduction program can improve the quality of the justice system even if it ultimately has little effort on case processing times.